Systematic review with meta‐analysis: direct comparisons of biomarkers for the diagnosis of fibrosis in chronic hepatitis C and B. Issue 1 (30th October 2015) - Houot, M.; Ngo, Y.; Munteanu, M.; Marque, S.; Poynard, T.
Summary: Background: Blood tests and transient elastography (TE), proposed as alternatives to biopsy for identifying advanced fibrosis (METAVIR‐stage‐F2 or greater) or cirrhosis, have never been compared using an intention to diagnose approach, with direct comparisons only, and Bayesian approach. Aim: To permit more appropriate comparisons. Methods: From an overview of articles (2002–2014), we selected studies that directly compared the diagnostic accuracy of FibroTest, aspartate aminotransferase–platelet ratio index (APRI), FIB4 or TE, with biopsy as a reference, in patients with chronic hepatitis C (CHC) or B (CHB). Investigators abstracted and checked study details and quality by using pre‐defined criteria. Bayesian method in intention to diagnose was the primary outcome. Results: Of 1321 articles identified, 71 studies including 77 groups according to aetiology (All‐CB) were eligible: 37 Only‐C, 28 Only‐B and 12 Mixed‐C‐B. There were 185 direct comparisons between the area under the ROC curves (AUROCs), 99 for the diagnosis of advanced fibrosis and 86 for cirrhosis. In All‐CB, Bayesian analyses revealed significant AUROCs differences in identifying advanced fibrosis in favour of FibroTest vs. TE [credibility interval: 0.06(0.02–0.09)], FibroTest vs. APRI [0.05 (0.03–0.07)] and for identifying cirrhosis TE vs. APRI [0.07 (0.02–0.13)] and FIB4 vs. APRI [0.04(0.02–0.05)]. No differences were observed between TE and FibroTest, for identifying cirrhosis in All‐CB, and in sub‐groups (Only‐C, Only‐B, Mixed‐CB) for both cirrhosis and fibrosis. Conclusions: In CHC and CHB, APRI had lower performances than FIB‐4, TE and FibroTest. TE had lower performance than FibroTest for identifying advanced fibrosis in All‐CB, without significant difference for identifying cirrhosis in all groups.